ANALISIS PENGARUH FUNDING, LENDING, DAN LOAN TO DEPOSIT RATIO TERHADAP KINERJA KEUANGAN DI PT BPR INDRA CANDRA SINGARAJA - KADEK DIAN AYUNING SARI; MERTYANI SARI DEWI (Universitas Mahasaraswati K. Mataram, 2023)
Every company certainly wants to achieve maximum profits. The company of PT BPR Indra Candra Singaraja during the covid-19 period experienced unstable profitability. The decline in profitability due to the Covid-19 pandemic can be seen in the financial reports on the ROA ratio from 2019-2022 at PT BPR Indra Candra Singaraja. In the world of banking, the main activities are raising funds and channeling funds. There is a soundness level of a bank that can be measured in terms of the Loan to Deposit Ratio which can describe whether or not a company is healthy.The purpose of this study was to determine the Effect of Funding, Lending, and Loan to Deposit Ratio on Financial Performance at PT. BPR Indra Candra Singaraja. The research method used is a quantitative method. The data analysis technique used in this study is multiple linear regression analysis, classical assumption test, determination analysis, f-test and t-test using the SPSS program. The results showed that funding had an effect on Financial Performance in Profitability of 0.025 units or 11.5% with the T test (2.342> 1.677). The effect of lending on financial performance in profitability is 0.018 units or 5.7% with the T test (2.070> 1.677) and the effect of the loan to deposit ratio on financial performance in profitability is 0.025 units or 8.2% with the T test it is found that (2.022> 1.677). Based on the results of the F-test simultaneously the variables funding, lending, and loan to deposit ratio have an effect on Financial Performance in Bank Profitability with the results of the F-Test hypothesis testing it was found that f-count>f-table (5.029> 1.677) with a significant level of 0.004 <0.05..